Karakter Spasial Ruang Publik sebagai Tempat Ketiga Studi Kasus: Pasar Seni dan Wisata Gabusan - Ratih T.A.K., A.A.Ayu (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2022)
Â The third place is a place to unwind, apart from home as the first place and the office as the second place. The third place is one type of public space. Gabusan Art and Tourism Market (PSWG) is a place for art accommodation in Bantul Regency, Yogyakarta. However, in recent years, the situation of PSWG as a public space has declined and is getting worse. It is necessary to conduct research related to the character of the third place as a public space. This qualitative, grounded theory research method uses primary sources: observations and interviews, and secondary sources: literature studies with the third-place theory from Ray Oldenburg. The research variable is that the third-place functions as a public space, a social space and own good accesibility. The stages of the research process starting from secondary data processing, namely literature studies, then primary data processing, namely observations and interviews of activity actors. The research results show that PSWG as a public space is sufficient, but as a third-place it is lacking in terms of social activities and accessibility